Desarrollo de una aplicación móvil multiplataforma como ayuda pedagógica para evaluación foniátrica perceptual (2022)
Perceptual phoniatric evaluation is a technique widely used in voice evaluation, it depends both on the expertise and experience of the person performing it and is an important complement for a final diagnosis and therefore an adequate treatment. Although there are currently several ways to approach the method, there are few technological tools that help to train in the process. This project is developed under the framework 'Ionic', which combined with web technologies (HTML, JavaScript and CSS) and some Information and Communication Technologies, concludes with an application easily accessible on computers, smartphones and Android tablets, where the user will have access to the application from anywhere with internet connection. The application is made up of different functions that allow both training and evaluation to test the student's skills; it also has a personalized tracking system in a comfortable and intuitive interface. This paper describes the process of design, implementation and deployment of the application, which, observed as a training system, can become an effective and efficient tool for the development of skills in the recognition of pathologies related to the perceptual evaluation of the voice for both professionals and students, the results obtained from a survey developed to measure the usability of the application are also shown